5α-Hydroxyeudesm-4(15),11(13)-dien-8β,12-olide - Gao, Xue (International Union of Crystallography, 2012)
The title compound, C(15)H(20)O(3), a sesquiterpene lactone, was isolated from the aerial parts of Carpesium minus Hemsl. (Compositae). The molecule is composed of three rings, with the two cyclohexane rings in chair conformations and the cyclopentane ring adopting a twist conformation. The A/B ring junction is trans-fused. The absolute configuration shown has been arbitrarily assigned. In the crystal, molecules are linked into [100] chains by O—H⋯O hydrogen bonds.